Vestibular schwannoma of oscillating size: A case report and review of literature - Rahmathulla, Gazanfar (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: Vestibular schwannomas are benign brain tumors arising from the 8th cranial nerve with a varying natural history. Various reports have described discernable growth patterns for these tumors. However, growth predictability remains low because of slow and indeterminate changes over time with follow-up reports not usually exceeding 3 years. Our report describes the long-term follow-up of an unusual cystic schwannoma with growth patterns prior to and following treatment, adding valuable information to the variable natural history and outcome of these infrequent tumors. CASE DESCRIPTION: A 68-year-old gentleman presented with a left-sided cystic vestibular schwannoma, initially managed conservatively. Imaging revealed wide variations in the size of his tumor over a period of 3 years. He was finally treated with Gamma Knife radiosurgery, and at 1 year following treatment shows tumor shrinkage with a change in tumor morphology. CONCLUSION: To our knowledge, the present case represents the first instance of a schwannoma showing wide fluctuations in tumor size and morphology over a period of time, with a good response to radiosurgery. We emphasize in this report that there is no “one size fits all” treatment paradigm for these tumors and each patient requires individualized care and intervention, taking into account their differing natural histories.